Slow Release Metformin Effect in Weight Loss and Total Calorie Intake in Obese Volunteers - Cholis Abrori; Lucky Tiya; Deti Rosalina (Journal of Agromedicine and Medical Sciences, 2017)
Obesity can cause serious problems that will lead to poor quality of life, increased morbidity and mortality rate. Slow-release metformin will work longer in the body with a single dose everyday be an alternative drug for weight loss. The purpose of this study was to compare the effectiveness of slow-release metformin compared to metformin regular to body weight and calorie intake in volunteers with obesity. The study was conducted on 16 volunteers who were divided into two groups in pairs. Volunteers will be measured weight and calorie intake with a 24-hour food recall method, data was taken at the time before the intervention, the end of week 1st, 2nd, 3rd, and 4th. The result obtained weight loss better in the group receiving slow-release metformin by 5.08% compared to the group receiving regular metformin by 2,60%, but there was no significant difference between the groups in terms of calorie intake during the study. The conclusion of this study is a slow-release metformin is greater in weight loss than regular metformin, but does not affect the amount of calorie intake.Keywords: Metformin, slow-release, weight loss, calorie intake, obesity